Variations on an old theme: maternity for women with a very successful professional career - Rocha-coutinho, Maria Lúcia (The Spanish Journal of Psychology, 2008)
In this study, relationships of middle-class women from Rio de Janeiro with their family and work are presented. A series of events during the 20th century have changed woman’s identity, previously centered on the roles of mother and wife, so that, there are now other options for women. Carioca girls are currently educated to compete, seek greater professional growth, and value their independence. However, some social discourses still reinforce women’s former role the in the family. The notion that the mother-child unit is basic, universal, and, psychologically, the most appropriate, both for the child’s healthy development and the mother’s wholeness, is still firmly rooted. Motherhood is therefore one of the most complex and problematic matters for modern Carioca woman. Fifteen women with successful professional careers, residents of the city of Rio de Janeiro, varying in age from 30 to 40, and with children from 6 months to 3 years of age, were interviewed. The interviews had an invisible structure, were recorded and transcribed. The discourse of the resultant texts was analyzed, using the categories I established. In this project, I focus on the results of the analysis of the category ¨View of Maternity¨ of the interviewed women.